Development of Cash-Free Branches in Poland - Witczak, Zbigniew (Journal of Finance and Financial Law, 2024)
The purpose of the article. The aim of the article is to analyze the Polish banking market from the perspective of the development of non-cash branches in correlation with the growing popularity of non-cash transactions. Evaluation of development opportunities in this area in the context of a decrease in the number of branches and an increase in the standard of modern technology.Methodology. The work uses the method of analysis, critical analysis, descriptive and comparative analysis of literature and reports of the banking sector.Results of the research. The Polish banking market is focusing more and more attention on the promotion of transactions by customers. The traditional model of a bank branch or contact center is no longer effective and competitive and requires changes. New solutions and focus on customer needs are needed to improve the operations of banking sector institutions. New technologies, the use of AI, support automation and a new approach to service, such as the growing network of non-cash branches, offer a chance to be a leader on the Polish banking market for servicing individual customers.